Encapsulation of Commensal Skin Bacteria within Membrane‐in‐Gel Patches. Issue 7 (31st January 2022) - Xu, Wanlin; Nouri, Peyman Malek Mohammadi; Demoustier‐Champagne, Sophie; Glinel, Karine; Jonas, Alain M.
Abstract: The commensal skin bacterium Staphylococcus epidermidis ( S. epidermidis ) provides a range of benefits to human hosts, contributing to skin equilibrium and good health, even though specific strains also act as pathogens if entering the host body. Therefore, skin‐applicable devices allowing to benefit from some factors secreted by S. epidermidis while keeping the bacteria at a desired location are important for the development of bacteriotherapeutical applications. Here, a membrane‐based gel patch is fabricated to trap S. epidermidis while keeping its metabolic activity. The pores of a track‐etched membrane are modified with layer‐by‐layer (LbL) multilayers to anchor bacteria, followed by coating the membrane with a thick layer of agarose gel, leading to a membrane‐in‐gel soft patch. LbL multilayers comprising antibacterial polycations are then deposited over the patch. By varying the multilayer composition, thickness and nature of the last layer, both probability of escape and metabolic activity of entrapped bacteria can be tuned. Poly(ethyleneimine)‐comprising multilayers prove to be particularly well‐suited for the fine control of bacterial escape and activity. These bacterial patches are thus complex living materials in which the living component is controlled by a careful combination of soft macromolecular components. Abstract : Skin‐applicable devices allowing to benefit from Staphylococcus epidermidis while preventing its uncontrolled proliferation are important for the development of bacteriotherapeutical applications. Here, bacteria are anchored within the pores of a membrane coated with a thick layer of agarose gel surrounded by an antibacterial shell, leading to a bacteria‐containing membrane‐in‐gel soft patch in which bacteria displays metabolic activity and limited proliferation.